The Role of Green Accounting in Improving Company Performance - Meini rotinsulu, Clara neltje (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to explore the role of Green Accounting in improving corporate sustainability, with a special focus on Insurance companies in Indonesia. Green Accounting is measured through three main indicators: Accounting reporting, Accounting costs, and Accounting investments. Corporate sustainability is assessed based on Accounting performance, social performance, and economic performance. The research method used is multiple linear regression analysis, with a sample consisting of 13 Insurance companies listed on the Indonesia Stock Exchange. The results of the study indicate that Green Accounting practices have a positive and significant effect on corporate sustainability. In addition, company size is found to be a moderating variable that strengthens the relationship between Green Accounting and corporate sustainability. This study confirms the importance of integrating Green Accounting into business strategies to achieve long-term sustainability goals. These findings provide practical implications for corporate management in improving sustainability performance through better Accounting investment and reporting. Recommendations for further research include expanding the sample and testing similar relationships in other industry sectors.